Aortic valve performance after remodelling versus reimplantation in a propensity-matched comparison - Gofus, Jan; Vojacek, Jan; Karalko, Mikita; Zacek, Pavel; Kolesar, Adrian; Toporcer, Tomas; Urban, Martin; Glac, Filip; Cerny, Stepan; Homola, Pavel; Hlubocky, Jaroslav; Slautin, Andrey; et al. (European journal of cardio-thoracic surgery : official journal of the European Association for Cardio-thoracic Surgery, 2024)
OBJECTIVES: Both aortic root remodelling and aortic valve (AV) reimplantation have been used for valve-sparing root replacement in patients with aortic root aneurysm with or without aortic regurgitation. There is no clear evidence to support one technique over the another. This study aimed to compare remodelling with basal ring annuloplasty versus reimplantation on a multicentre level with the use of propensity-score matching. METHODS: This was a retrospective international multicentre study of patients undergoing remodelling or reimplantation between 2010 and 2021. Twenty-three preoperative covariates (including root dimensions and valve characteristics) were used for propensity-score matching. Perioperative outcomes were analysed along with longer-term freedom from AV reoperation/reintervention and other major valve-related events. RESULTS: Throughout the study period, 297 patients underwent remodelling and 281 had reimplantation. Using propensity-score matching, 112 pairs were selected and further compared. We did not find a statistically significant difference in perioperative outcomes between the matched groups. Patients after remodelling had significantly higher reintervention risk than after reimplantation over the median follow-up of 6 years (P = 0.016). The remodelling technique (P = 0.02), need for decalcification (P = 0.03) and degree of immediate postoperative AV regurgitation (P < 0.001) were defined as independent risk factors for later AV reintervention. After exclusion of patients with worse than mild AV regurgitation immediately after repair, both techniques functioned comparably (P = 0.089). CONCLUSIONS: AV reimplantation was associated with better valve function in longer-term postoperatively than remodelling. If optimal immediate repair outcome was achieved, both techniques provided comparable AV function.
Keywords: dospělí; Cardiac Valve Annuloplasty; tendenční skóre; Female; Replantation; Heart Valve Prosthesis Implantation; aortální chlopeň; anuloplastika srdeční chlopně; Adult; výsledek terapie; ženské pohlaví; chirurgická náhrada chlopně; replantace; lidé; aortální insuficience; Aortic Valve Insufficiency; Treatment Outcome; Reoperation; reoperace; retrospektivní studie; Male; Aged; Aortic Valve; lidé středního věku; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; Propensity Score; Humans